2015
DOI: 10.1007/s00253-015-7102-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Rhodosporidium toruloides with a membrane transporter facilitates production and separation of carotenoids and lipids in a bi-phasic culture

Abstract: The oleaginous yeast Rhodosporidium toruloides has great biotechnological potential. It accumulates a high amount of lipids which can be used for biofuels and also produces carotenoids which are valuable in the food and pharmaceutical industry. However, the location of these two hydrophobic products in the cell membrane prohibits its efficient harvesting and separation. Here, the transporter Pdr10 was engineered into R. toruloides and cultured in two-phase media containing oil. This enabled the production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…3 There are several strategies to improve the economic feasibility of MLs: rst of all, exploration of low cost substrates such as lignocellulosic biomass and various organic wastes; 4,5 second, developing more efficient culture strategies and product separation methods to reduce process costs; 6 in another scenario, manufacturing valuable (co-)products such as unsaturated fatty acids and carotenoids through metabolic engineering of oleaginous species. 7,8 However, the theoretical yield of per mole of hexose is limited to two moles acetyl-CoA, since the glycolysis loses a carbon equivalent for each C3 unit upon pyruvate decarboxylation. 9 Ideally, cell growth and lipid production may be further improved by devising more efficient acetyl-CoA generating pathways, but such efforts remain limited in oleaginous yeast.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are several strategies to improve the economic feasibility of MLs: rst of all, exploration of low cost substrates such as lignocellulosic biomass and various organic wastes; 4,5 second, developing more efficient culture strategies and product separation methods to reduce process costs; 6 in another scenario, manufacturing valuable (co-)products such as unsaturated fatty acids and carotenoids through metabolic engineering of oleaginous species. 7,8 However, the theoretical yield of per mole of hexose is limited to two moles acetyl-CoA, since the glycolysis loses a carbon equivalent for each C3 unit upon pyruvate decarboxylation. 9 Ideally, cell growth and lipid production may be further improved by devising more efficient acetyl-CoA generating pathways, but such efforts remain limited in oleaginous yeast.…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae strain (CEN.PK113-7D) can induce multidrug-resistant transporter synthesis, encoded by pleiotropic drug-resistance genes (Pdr10), and concluded that this can facilitate the secretion of carotenoids to the environment to decrease the toxicity within the cells. Based on these results, Lee et al [ 17 ] transformed Pdr10 from S . cerevisiae into Rhodosporidium toruloides , and found that Pdr10 strain cultivated in the two-phase media could obtain higher production of carotenoids due to continuous export of carotenoids in situ.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that the oleaginous yeast R. toruloides can naturally accumulate high levels of carotenoids. Recently, a membrane transporter Pdr10 was introduced into R. toruloides to facilitate production and separation of carotenoids ( Lee et al, 2016 ). In the resulting strain, a total of 2.9 μg/mg carotenoids was produced, while a total of 1.8 μg/mg carotenoids was exported.…”
Section: Engineering Oleaginous Yeasts For Production Of Fuels and Chmentioning
confidence: 99%